2010
DOI: 10.1016/j.jccase.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent takotsubo cardiomyopathy can appear as transient midventricular ballooning syndrome

Abstract: We report a rare female case of typical takotsubo cardiomyopathy at the first admission and recurrent takotsubo cardiomyopathy with a unique pattern of contraction at the second admission. The condition manifested as akinesis in the middle portion of the left ventricle and hyperkinesis of the apex and base. Our case indicates that recurrent takotsubo cardiomyopathy can appear as transient midventricular ballooning syndrome, but it remains to be determined whether both diseases have a tendency to coexist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…25 Conversely, provoked coronary spasm cases in patients with TTC have been reported and their variants from the early era of discovering this syndrome to the present. 1,6,[33][34][35][36][37][38][39][40] This discrepancy in the relationship between TTC and spasm may be due to the sensitivity of the ACh provocation test. Sueda et al reported that intracoronary injection of ACh is less sensitive for diagnosis in young patients with rest angina and recommend performing sequential spasm provocation tests of ACh and ergonovine.…”
Section: Discussionmentioning
confidence: 99%
“…25 Conversely, provoked coronary spasm cases in patients with TTC have been reported and their variants from the early era of discovering this syndrome to the present. 1,6,[33][34][35][36][37][38][39][40] This discrepancy in the relationship between TTC and spasm may be due to the sensitivity of the ACh provocation test. Sueda et al reported that intracoronary injection of ACh is less sensitive for diagnosis in young patients with rest angina and recommend performing sequential spasm provocation tests of ACh and ergonovine.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient is unique in that she had a recurrence of this syndrome within seven months of her initial presentation, and both episodes were preceded by transient neurological complaints. Recurrence of TTC, once thought to be rare, has been increasingly recognized in the literature, with a recurrence rate of 5% to 10% worldwide [ 2 , 4 , 5 ]. Additionally, the development of TTC in the setting of fleeting neurological symptoms such as aphasia and ataxia without structural brain disease has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, LV function returns to normal within six to eight weeks. Recurrence, which is increasingly being reported in the literature [ 2 , 4 , 5 ], can be related to neurological pathology [ 6 , 7 ]. We present a case of a woman with recurrent TTC whose presenting symptoms on both occasions were of neurological origin.…”
Section: Introductionmentioning
confidence: 99%
“…However, several variants of TC have been described. The midventricular type is characterized by akinesis with or without ballooning of the midventricular segment and a hyperdynamic pattern of base and apex [3]. The exact pathophysiology of TC is still unclear, although several hypotheses, such as multivessel coronary spasm, microvascular impairment and direct catecholamine-mediated myocardial stunning, have been proposed [4].…”
Section: Introductionmentioning
confidence: 99%